2014
DOI: 10.1186/2051-5960-2-67
|View full text |Cite
|
Sign up to set email alerts
|

Selective vulnerability of the cerebral vasculature to blast injury in a rat model of mild traumatic brain injury

Abstract: BackgroundBlast-related traumatic brain injury (TBI) is a common cause of injury in the military operations in Iraq and Afghanistan. How the primary blast wave affects the brain is not well understood. The aim of the present study was to examine whether blast exposure affects the cerebral vasculature in a rodent model. We analyzed the brains of rats exposed to single or multiple (three) 74.5 kPa blast exposures, conditions that mimic a mild TBI. Rats were sacrificed 24 hours or between 6 and 10 months after ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
67
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 52 publications
9
67
0
Order By: Relevance
“…It was reported that the earliest pathological findings after 24 h of exposure to blast are the presence of blood in ventricles and choroid plexus [31, 32]. This occurs even after exposures to mild blast intensities (74.5 kPa) which can be attributed to the direct shearing effects of blast on the choroid plexus leading to vascular rupture and leakage of blood into the ventricles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the earliest pathological findings after 24 h of exposure to blast are the presence of blood in ventricles and choroid plexus [31, 32]. This occurs even after exposures to mild blast intensities (74.5 kPa) which can be attributed to the direct shearing effects of blast on the choroid plexus leading to vascular rupture and leakage of blood into the ventricles.…”
Section: Discussionmentioning
confidence: 99%
“…Confocal images have shown strong widespread EB fluorescence in cortex after blast [14] and the optical density of EB in frontal cortex of blast group was over 60% higher than the sham group [11]. It was reported that focal lesions were present in many brain regions including the cortex, which were likely caused by direct shear effects induced by blast [31, 32]. Both, changes in ICP and EB leakage were related to the BOP intensity with a more pronounced effect observed in multiple exposures to the higher levels of BOP.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our group has also shown an upregulation of pro-inflammatory markers in a rat model of blast injury (16). A significant difference in iNOS mRNA abundance was observed in the ipsilateral S1BF region after blast (F (2, 12) = 5.60; P < 0.05). We revealed a significant increase in iNOS mRNA abundance at 24 hours post-blast when compared to control animals (q = 3.21; P < 0.05) (Figure 7A).…”
Section: Resultsmentioning
confidence: 94%
“…A significant difference in GFAP mRNA abundance was observed in the ipsilateral S1BF region after blast (F (2, 12) = 5.73; P < 0.05). We revealed a significant increase in GFAP mRNA abundance at 24 hours post-blast when compared to control animals (q = 3.36; P < 0.05) (Figure 5A).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation